LA’IBUN WA LAHWUN DALAM AL-QUR‘AN (Suatu Tinjauan Tafsir Tematik) - Mashuri Rifai; Nurdin Nurdin (Jurnal Ushuluddin Adab dan Dakwah, 2020)
Lai'bun wa lahwun in Al-Qur'an, a thematic interpretation which means play and joking. This term is expressed in the Al-Qur'an 31 times in various forms, both independently and in conjunction. The problem in this paper is how the views of the Mufassirs and the concept of la'ibun wa lahwun in the Al-Quran. In this discussion, the writer uses descriptive method in studying the concept of la'ibun wa lahwun in the Al-Qur'an, the same method is also used to get a clear picture of the perspective of the Al-Qur'an regarding la'ibun wa lahwun. Furthermore, to obtain an overview of the principles of la'ibun wa lahwun in the Al-Qur'an, the author uses the critical analysis method. the result is the theme of La'ibun wa lahwun in the Al-Qur'an, so the author comes to the conclusion that the concept of la'ibun wa lahwun in the Al-Qur'an is anything that can make the perpetrator neglectful of Allah's commands.